Governmental power under the Fifth French Republic - Bertrand, Mathieu (Journal of the Belarusian State University. Law, 2019)
The executive power really is a governmental power. Whether it is in the hands of a President or a Prime Minister, depending on the political regime, it relates to the fundamental interests of the Nation or the State’s policy. The system according to which the Parliament votes the law and the executive enforces it, is a fiction. In France, as in most parliamentary democracies, the Government or the Head of the State decides the policy of the State. It receives the legitimacy to do so from popular elections. Majority rule, let alone institutional differences, implies that the People choose who occupies the seat of executive power. The issue before us is to know who controls the executive functions of government in Western democracies. In the French system, the answer can seem ambiguous. The presidential and legislative elections of 2017 reflect the permanence of these structuring elements of the Fifth Republic.